2000
DOI: 10.1053/rmed.2000.0803
|View full text |Cite
|
Sign up to set email alerts
|

Airway obstruction and chronic exertional dyspnoea in patients with persistent bronchial asthma

Abstract: In patients with COPD, flow limitation (FL) predicts chronic exertional dyspnoea (CED) better than routine spirometry. Whether, and to what extent, FL and CED are overlapping quantities in chronic asthma has not yet been defined. Forty consecutive clinically stable asthmatic patients without smoking history or cardiopulmonary disorders, were studied. In each subject respiratory function, including static and dynamic pulmonary volumes, was evaluated; maximal (MEFV) and partial (PEFV) expiratory V'-V curves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…[33], Table 5). By contrast Filippelli et al [34], using partial FEFV curves, found that half of their asthmatic patients exhibited tEFL, closer to our patients' prevalence of tEFL (64%). Again, differences can be attributed to volume and time history and time-constant inequalities within the lung [33] [35].…”
Section: Critique Of Use Of the Forced Expiratory Flow-volume Curvesupporting
confidence: 55%
“…[33], Table 5). By contrast Filippelli et al [34], using partial FEFV curves, found that half of their asthmatic patients exhibited tEFL, closer to our patients' prevalence of tEFL (64%). Again, differences can be attributed to volume and time history and time-constant inequalities within the lung [33] [35].…”
Section: Critique Of Use Of the Forced Expiratory Flow-volume Curvesupporting
confidence: 55%
“…Corticosteroids have been found to be effective in the management of dyspnea associated with asthma [3,4], chronic obstructive pulmonary disease [5,6], and carcinomatosis lymphangitis [7,8]. Moreover corticosteroids are effective in the treatment of upper respiratory obstruction because of hemangioma in children [9][10][11].…”
Section: Discussionmentioning
confidence: 99%